Working Women Coping Strategy In Facing Work Conflict - Retno Dwiyanti; Ratna Kartikawati (Technium Social Sciences Journal, 2020)
This research is motivated by the conflicts that often occur in women workers in the workplace. Facing conflicts experienced, every human being has their own way of dealing with it. One strategy in dealing with conflict is coping, which is the response of individuals to overcome problems. The purpose of this study was to determine the coping strategies of working women against work conflicts. This study uses a quantitative approach. Respondents in this study were 44 working women in a private tertiary institution in Indonesia. The instrument used in data collection uses the scale of problem focus coping, the scale of emotional focus coping, and the scale of a work conflict. The results showed that there was a significant effect of emotional focus coping on work conflict, but the effect of problem focus coping on work conflict was not significant.